Keefektifan Counter Preassure Massage terhadap Intensitas Nyeri Kala I Fase Aktif Persalinan di Puskesmas Rawat Inap Langgam Kabupaten Pelalawan - Isrowiyatun Daiyah (EMBRIO, 2020)
The highest degree of pain in the process of childbirth among other pains. About 36.35% mothers experienced obstetric complications in Langgam Health Center with 14.1 being caused by prolonged labor. One of natural techniques to relieve labor pain to women in labor is by offering Counter Pressure Massage. This study aimed to analyze the impact of Counter Pressure Massage on the intensity of labor pain in active phase of the first stage of labor. This research was pre experimental with One Group Pretest and Posttest design. The population was 45 people and the sample was 15 people. The research was conducted at Langgam Inpatient Health Center in February-June 2017. Data analysis used dependent samples t-test. This study found that there was a significant decrease in the intensity of labor pain after the treatment of Counter Pressure Massage (p = 0.000). This study concluded that Counter Pressure Massage technique is very influential to reduce the intensity of labor pain. Health workers are expected to apply this massage as one of delivery services in reducing pain